Quantity judgments in the context of risk/reward decision making in striped field mice: first “count,” then hunt - Panteleeva, Sofia; Reznikova, Zhanna; Vygonyailova, Olga (Frontiers in Psychology, 2013)
We simulated the vital situation of risky hunting in the striped field mouse Apodemus agrarius in order to examine whether these animals are able to make a choice between small and large quantities of live prey (ants). In the first (preliminary) experiment we investigated to what extent mice were interested in ants as a live prey and how their hunting activity depended on the quantity of these edible but rather aggressive insects. We placed mice one by one into arenas together with ant groups of different size, from 10 to 60. Surprisingly, animals, both wild-caught and laboratory-reared, displayed rather skilled predatory attacks: mice killed and ate from 0.37±003 to 4±0.5 ants per minute. However, there was a threshold number of ants in the arenas when rodents expressed signs of discomfort and started to panic, because ants bit them. This threshold corresponds to the dynamic density (about 400 individuals per m 2per min) in the vicinity of anthills and ants’ routes in natural environment. In the second experiment mice had to choose between different quantities of ants placed in two transparent tunnels. Ants here served both as food items and as a source of danger. As far as we know, this is the first experimental paradigm based on evaluation of quantity judgements in the context of risk/reward decision making where the animals face a trade-off between the hedonistic value of the prey and the danger it presents.. We found that when mice have to choose between 5 vs 15, 5 vs 30 and 10 vs 30 ants, they always tend to prefer the smaller quantity, thus displaying the capacity for distinguishing more from less in order to ensure comfortable hunting. The results of this study are ecologically relevant as they reflect situations and challenges faced by free-living small rodents.